Campanha de conscientização sobre a paralisia do sono - Aguiar, Lucas Sicsú Gomes (Brasil, 2024)
Exploring sleep paralysis, an intriguing and often overlooked phenomenon, this study aims to increase interest and awareness on the subject through the development of an awareness campaign using design and animation. Drawing upon a systematic review by Sharpless and Barber (2011), spanning five decades of international and intercultural research on sleep paralysis patients, it is noted that many individuals lack knowledge about the phenomenon until experiencing a first episode. The motivation behind this work is to provide information so that more people can identify and treat sleep paralysis efficiently and preemptively, thereby reducing the occurrence of traumatic episodes and improving sleep quality and health. The research proposes an awareness campaign, utilizing design and animation as tools to educate and inform the public about this sleep disorder.